Simulations of Measured Photobleaching Kinetics in Human Basal Cell Carcinomas Suggest Blood Flow Reductions During ALA-PDT - Wang, Ken Kang-Hsin (2009)
BACKGROUND AND OBJECTIVE: In a recently completed pilot clinical study at Roswell Park Cancer Institute, patients with superficial basal cell carcinoma (sBCC) received topical application of 20% 5-aminolevulinic acid (ALA) and were irradiated with 633 nm light at 10–150 mW cm(−2). Protoporphyrin IX (PpIX) photobleaching in the lesion and the adjacent perilesion normal margin was monitored by fluorescence spectroscopy. In most cases, the rate of bleaching slowed as treatment progressed, leaving a fraction of the PpIX unbleached despite sustained irradiation. To account for this feature, we hypothesized a decrease in blood flow during ALA-photodynamic therapy (PDT) that reduced the rate of oxygen transported to the tissue and therefore attenuated the photobleaching process. We have performed a detailed analysis of this hypothesis. STUDY DESIGN/MATERIALS AND METHODS: We used a comprehensive, previously published mathematical model to simulate the effects of therapy-induced blood flow reduction on the measured PpIX photobleaching. This mathematical model of PDT in vivo incorporates a singlet-oxygen-mediated photobleaching mechanism, dynamic unloading of oxygen from hemoglobin, and provides for blood flow velocity changes. It permits simulation of the in vivo photobleaching of PpIX in this patient population over the full range of irradiances and fluences. RESULTS: The results suggest that the physiological equivalent of discrete blood flow reductions is necessary to simulate successfully the features of the bleaching data over the entire treatment fluence regime. Furthermore, the magnitude of the blood flow changes in the normal tissue margin and lesion for a wide range of irradiances is consistent with a nitric-oxide-mediated mechanism of vasoconstriction. CONCLUSION: A detailed numerical study using a comprehensive PDT dosimetry model is consistent with the hypothesis that the observed trends in the in vivo PpIX photobleaching data from patients may be explained on the basis of therapy-induced blood flow reductions at specific fluences.